Visualisation of hypertension: A non-randomised pilot study to explore the feasibility of a Community Pharmacy-based intervention to support medication adherence (Hi-BP) - Sarah L. Brown; Barry J. McDonnell; David McRae; Paul Angel; Imtiaz Khan; Rhiannon Phillips; Britt Hallingberg; Delyth H. James (PLoS ONE, 2026)
Using visualisation to conceptualise a chronic condition can encourage accurate illness beliefs and support treatment adherence. Hi-BP is a digital visual intervention to support adherence to antihypertensive medication, co-produced with patients. The aim of this study was to investigate the feasibility and acceptability of Hi-BP and explore the preliminary direction of effects on illness and treatment beliefs, medication adherence and blood pressure (BP). A two-phased mixed-methods non-randomised feasibility study was conducted from April 2021 to March 2022 in eight community pharmacies across one Health Board in South-East Wales, UK. Hi-BP was delivered as a single researcher-led consultation to 69 patients in Phase 1 and by pharmacists to three patients in Phase 2. Feasibility was determined using predefined criteria, with acceptability explored qualitatively using semi-structured interviews. Quantitative outcome measures ( illness perceptions, medication beliefs, medication-adherence, prescription dispensing and collection data, BP) were recorded at baseline and immediately post-intervention.Follow-up outcome measures were collected at two-weeks ( medication-adherence ) and three-months ( all baseline measures ). Hi-BP met feasibility criteria for pharmacist recruitment in both phases, and patient recruitment in Phase 1, but not Phase 2. Hi-BP was acceptable to the sub-sample of 15 patient participants interviewed in Phase 1; insufficient data were available to determine patient acceptability at Phase 2. Hi-BP was acceptable to pharmacists in Phase 1 and partially acceptable at Phase 2, due to competing demands on time for intervention delivery. All outcome measures were considered feasible for use, though a ceiling effect was noted for medication adherence. A potentially positive directional effect was found for illness perceptions (X 2 (2)=10.83,n=54,p=0.004), medication beliefs (BMQ-Necessity (X 2 (2)=11.71,n=54,p=0.003) and BP (Systolic BP Z=-3.91,n=51,p=<0.001) but not for medication adherence (MARS-5 X 2 (2)= 2.4,n=45,p=0.299). In the Community Pharmacy setting, Hi-BP was well-accepted and has the potential for significant reductions in BP; however, further research is needed to explore pharmacist capacity to support implementation.